Rhinovirus induces an anabolic reprogramming in host cell metabolism essential for viral replication - Gualdoni, Guido A. (Proc Natl Acad Sci U S A, 2018)
Rhinoviruses (RVs) are responsible for the majority of upper airway infections; despite their high prevalence and the resulting economic burden, effective treatment is lacking. We report here that RV induces metabolic alterations in host cells, which offer an efficient target for antiviral intervention. We show that RV-infected cells rapidly up-regulate glucose uptake in a PI3K-dependent manner. In parallel, infected cells enhance the expression of the PI3K-regulated glucose transporter GLUT1. In-depth metabolomic analysis of RV-infected cells revealed a critical role of glucose mobilization from extracellular and intracellular pools via glycogenolysis for viral replication. Infection resulted in a highly anabolic state, including enhanced nucleotide synthesis and lipogenesis. Consistently, we observed that glucose deprivation from medium and via glycolysis inhibition by 2-deoxyglucose (2-DG) potently impairs viral replication. Metabolomic analysis showed that 2-DG specifically reverts the RV-induced anabolic reprogramming. In addition, treatment with 2-DG inhibited RV infection and inflammation in a murine model. Thus, we demonstrate that the specific metabolic fingerprint of RV infection can be used to identify new targets for therapeutic intervention.